Implications of Implementing Teacher Training Programs on Improving Teacher Work Performance Through IHES -Based Teaching Practices - Sapie Sabilan; Mohd Isa Hamzah; Zakiah Hassan; Suziana Hanini Sulaiman (Universiti Sains Islam Malaysia, 2024)
Journal of Quran Sunnah Education and Special Needs Volume 8 Issue 1 Page (12-23)